To err is…Drug? Patient? Doctor? Healthcare System? - Kumar, Bhargavi; Thangavelu, Saravanan; Shukkoor, Aashiq Ahamed; Kanthimathi, Nandhini Ramakrishnan (Indian Journal of Pharmacy Practice)
Medicine is a practicing art. This is because we evolve constantly with everyday learning. The core of the health care system is management of patients with pharmacological measures. However the role of the health care deliverers does not stop with prescribing drugs. It is of central importance to be aware of the potential side effects of the drug including the rarest of the complications. It is equally important to discuss with our patients the available choices, the risk - benefit ratio and counsel them accordingly regarding anticipated common and rare side effects. The patient must be repeatedly reinforced about the importance of periodic follow up with the doctor, need for regular laboratory monitoring and reporting of alarm signs without any delay. Thus patient education, awareness of drug characteristics and a detailed doctor prescription are central in avoiding as well as managing drug related adverse effects. Here we present a case series of 9 different patients presenting with varied drug related adverse effects.
Keywords: Adverse drug reactions; Periodic Monitoring; Patient education; Warning signs; Physician role.